2014
DOI: 10.1039/c4ra02283a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric lubricating films directly at the sliding interface via mechanochemical reactions of allyl alcohols adsorbed from the vapor phase

Abstract: Friction initially occurs in a vapor environment, during which a triboproduct is formed. This triboproduct lubricates in absence of the vapor for over 30 000 reciprocating cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 31 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…For self-mated stainless steel sliding contact, allyl alcohol gave a friction coefficient of ~0.2 at a vapor partial pressure of 15% and higher, which is much lower than the friction of stainless steel in dry condition (higher than 1). It was also found that the adsorbed allyl alcohol molecules were polymerized only within the contact area during sliding [225]. No wear was found after sliding was stopped indicating that the tribo-products were not by-products of stainless steel wear.…”
Section: Mechanochemical Synthesis Of Nano-lubricant Films From Vapormentioning
confidence: 80%
See 2 more Smart Citations
“…For self-mated stainless steel sliding contact, allyl alcohol gave a friction coefficient of ~0.2 at a vapor partial pressure of 15% and higher, which is much lower than the friction of stainless steel in dry condition (higher than 1). It was also found that the adsorbed allyl alcohol molecules were polymerized only within the contact area during sliding [225]. No wear was found after sliding was stopped indicating that the tribo-products were not by-products of stainless steel wear.…”
Section: Mechanochemical Synthesis Of Nano-lubricant Films From Vapormentioning
confidence: 80%
“…No wear was found after sliding was stopped indicating that the tribo-products were not by-products of stainless steel wear. Unlike the wearinduced tribo-polymerization of adsorbed pentanol vapor on silicon oxide [216], the formation of allylalcohol tribo-product was attributed to polymerization of the unsaturated C=C bond to form a polymerized alcohol [225]. When allyl alcohol vapor flow was stopped, the tribo-polymer was sufficient to lubricate the sliding contact.…”
Section: Mechanochemical Synthesis Of Nano-lubricant Films From Vapormentioning
confidence: 93%
See 1 more Smart Citation
“…[13,14,18] Recently, it has been shown that allyl alcohol adsorbed on stainless steel could be polymerized under interfacial shear conditions. [19] Even though allyl alcohol has a double bond, it does not undergo typical radical polymerization in thermal reaction conditions. [20] However, it was easily polymerized under the mechanical shear condition.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the tribo-polymer produced from allyl alcohol at the sliding track acted as a boundary lubrication film for an extended period of time without continuous supply of lubricant vapor. [19] In this paper, we report tribochemical reactions of α-pinene (C 10 H 16 ) and pinane (C 10 H 18 ).…”
Section: Introductionmentioning
confidence: 99%